Government Initiative to Promote Cashless Transaction through Innovative Payment Solutions to provide ease and Safety to Pay Online - Muhammad Younus; Achmad Nurmandi; Wahdania Suardi; Hajra Gul (Formosa Journal of Applied Sciences, 2023)
The Motive of the research being done for this paper is to increase the importance of the cashless transaction, and it should be adopted by Merchants, Riders, and Customers to make payments at different phases come during Online shopping, which starts from Booking of the order and ends at order received at location. The reason for promoting the cashless transaction through this paper is to firstly provide ease and alternative of making the payment. Then secondly, to digitize and automate the way of making payments. Finally, through digitizing of payments made, the government can able to regulate better each transaction and money transfer, which helps in minimizing the size of the undocumented economy because it mainly runs on paper cash.